A comparison of line‐transect distance sampling methods for estimating gopher tortoise population densities - Traci D. Castellón; Betsie B. Rothermel; Saif Z. Nomani (Wildlife Society Bulletin)
ABSTRACT Line‐transect distance sampling (LTDS) is increasingly used to estimate gopher tortoise (Gopherus polyphemus) densities. The process requires detecting tortoise burrows, and then determining occupancy. We compared 3 LTDS approaches that differ in how burrow detection and occupancy data are integrated, and 2 search strategies. Surveys were conducted at Avon Park Air Force Range in South‐central Florida, USA, from April through October 2009. These include 1) LTDS using data from occupied burrows only; 2) LTDS with burrows treated as “clusters” of size 1 or 0 depending on occupancy; 3) LTDS to estimate burrow densities, with occupancy modeling to estimate occupancy rates; and 4) 2 search strategies: standard versus expanded searches. The LTDS method produced reliable burrow density estimates, and tortoise densities were estimated most precisely and with least effort using data from occupied burrows only. However, any method could be biased if burrow occupancy is uncertain. Indeed, in the Florida scrub and pine flatwoods habitats, video‐camera scoping was hindered by groundwater or obstructions, resulting in undetermined occupancy for 45% of burrows. Improving scope technologies and surveying during the dry season has improved subsequent results for xeric habitats; however, research is needed to improve detectability of tortoises in mesic habitats with flooded burrows. If occupancy is uncertain, we recommend collecting data on all burrows, irrespective of occupancy, so that burrow densities can be estimated even if occupancy cannot. We do not recommend expanding the search area with sigmoid search paths adjacent to transects owing to potential violations of assumptions, nor use of occupancy modeling, because model requirements may lead to unacceptable exclusion of data. © 2015 The Wildlife Society.